Wages in high-tech start-ups: Do academic spin-offs pay a wage premium? - Matthias Dorner; Helmut Fryges; Kathrin Schopen (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2015)
Due to their origin from universities, academic spin-offs operate at the forefront of the technological development. Therefore, spin-offs exhibit a skill-biased labour demand, i.e. spin-offs have a high demand for employees with cutting edge knowledge and technical skills that distinguish them even from other high-tech start-up firms. In order to accommodate this demand, spin-offs may have to pay a relative wage premium compared to other high-tech start-ups. However, neither a comprehensive theoretical assessment nor the empirical literature on wages in start-ups unambiguously predicts the existence and the direction of wage differentials between spin-offs and non-spin-offs. This paper addresses this research gap and examines empirically whether or not spin-offs pay their employees a wage premium. Using a unique linked employer-employee data set of German high-tech start-ups, we estimate Mincer-type wage regressions applying the Hausman-Taylor panel estimator. Our results show that spin-offs do not pay a wage premium in general. However, a notable exception from this general result is that spin-offs that commercialise new scientific results or methods provide higher wages to employees with linkages to the university sector - either as university graduates or as student workers. – – Wegen ihres Ursprungs an Universitäten operieren akademische Spinoffs an der Spitze der technologischen Entwicklung. Sie haben daher auch im Vergleich mit anderen High-Tech Gründungen eine relativ hohe Nachfrage nach Arbeitskräften mit hochentwickeltem Wissen und technischen Fähigkeiten. Folglich müssen Spinoffs potenziell eine Lohnprämie zahlen, um hinreichend ausgebildete Arbeitskräfte auf dem externen Arbeitsmarkt zu attrahieren und diese im Unternehmen zu halten. Theoretische Studien zu Bestimmungsfaktoren von Löhnen liefern jedoch auch Gegenargumente, die für niedrigere Löhne in Spinoffs sprechen können. Die vorliegende Studie untersucht ob akademische Spinoffs tatsächlich eine Lohnprämie bezahlen und welche Bestimmungsfaktoren mögliche Lohnunterschiede erklären. Zu diesem Zweck werden umfangreiche Employer-Employee-Paneldaten erstellt und mittels Mincer Lohnregressionen sowie erweiterten Panel Schätzverfahren nach Hausman-Taylor analysiert. Die Ergebnisse zeigen, dass Beschäftigte in akademischen Spinoffs nicht grundsätzlich eine Lohnprämie erhalten. Eine Ausnahme von diesem generellen Befund stellen akademischen Spinoffs dar, die universitäre Forschungsergebnisse oder Methodenentwicklungen kommerzialisieren. Diese Firmen zahlen ausschließlich Beschäftigten mit akademischem Abschluss (sowie studentischen Mitarbeitern) signifikante höhere Löhne als vergleichbaren Beschäftigten in anderen Spinoffs bzw. High-Tech Gründungen.
Keywords: J31; L26; M13; O34; 330; wages; high-tech start-ups; academic spin-offs; linked employeremployee data